Intelligent Pillow for Heart Rate Monitor - Everlyn Chiang; Muthukumar Vellaisamy (Institute of Advanced Engineering and Science, 2013)
The aim of the project is to develop intelligent pillow to monitor the heart rate by using fiber optical sensor. The research is focused upon allowing more automation of patient care, an especially important matter for the elder population or bedridden patients, which is a rapidly growing fraction of much of the world population today. The fiber-optical sensor is built into pillow. Patients can determine their heart rate by just lying on the pillow and the device will not cause any disturbance to patients and at the same time still monitoring the heart rate. ECG electrodes and finger clip / ear lobe clip probes (using IR LED and photodiode technology) are commonly used for monitoring heart rate. Unfortunately, they are inconvenient and inadequate for long-term, everyday measurements. Fiber-optical sensing overcomes many of these challenges by using light rather than electricity and standard optical fiber in place of copper wire. Optical fibers are nonconductive, electrically passive, immune to electromagnetic interference (EMI)-induced noise, and able to transmit data over long distances with little or no loss in signal integrity. Using the concept of light and the benefits of using fiber optical sensors to detect the heart rate, PPG(photoplethysmogram) is being used in this project. A photoplethysmogram (PPG) is an optically obtained plethysmogram, a volumetric measurement of an organ. A PPG is often obtained by using a pulse oximeter which illuminates the skin and measures changes in light absorption (Shelley and Shelley, 2001).DOI:http://dx.doi.org/10.11591/ijece.v3i6.4050